2022
DOI: 10.2147/nss.s361518
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders in Children with Prader Willi Syndrome: Current Perspectives

Abstract: Children with Prader-Willi syndrome (PWS) face a multitude of potential health challenges including life-threatening obesity, endocrinopathies, behavioral and emotional dysregulation, developmental delays, and sleep disorders. In the current perspective piece, we provide a focused review of the condition's etiology and clinical findings, as well as a more in-depth discussion of sleep disorders frequently associated with PWS. In particular, we highlight and discuss difficult clinical scenarios frequently encoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…However, CSA, sleep-related hypoventilation, excessive daytime sleepiness, and altered sleep architecture are also described in high proportion in this population compared to that in healthy controls [ 3 , 12 ]. Brainstem immaturity, hypothalamic dysfunction, and abnormal chemosensitivity to CO 2 and O 2 are other contributing mechanisms to CSA in PWS infants [ 76 ]. In 2014, Cohen et al reviewed polysomnographic data of 44 PWS children (23 subjects with median age of 1.0 years and 21 subjects with median age of 5.1 years) and diagnosed sleep apnea in 25/44 (57%) subjects.…”
Section: Children With Complex Disordersmentioning
confidence: 99%
“…However, CSA, sleep-related hypoventilation, excessive daytime sleepiness, and altered sleep architecture are also described in high proportion in this population compared to that in healthy controls [ 3 , 12 ]. Brainstem immaturity, hypothalamic dysfunction, and abnormal chemosensitivity to CO 2 and O 2 are other contributing mechanisms to CSA in PWS infants [ 76 ]. In 2014, Cohen et al reviewed polysomnographic data of 44 PWS children (23 subjects with median age of 1.0 years and 21 subjects with median age of 5.1 years) and diagnosed sleep apnea in 25/44 (57%) subjects.…”
Section: Children With Complex Disordersmentioning
confidence: 99%
“…Sleep-related breathing disorders (SDBs) are common and potentially serious complications of PWS that can afect patients at any age. Multiple studies have reported a high prevalence of SDB among individuals with PWS ranging between 44 and 100%, compared to a prevalence of 2-3% in the general population [1][2][3]. Craniofacial dysmorphology afecting upper airway size, adenotonsillar hypertrophy, obesity, hypotonia, chest wall deformities, and defective ventilatory control due to hypothalamic dysfunction contribute to the overall high prevalence of SDB in PWS [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Prader-Willi syndrome (PWS) is a rare genetic disorder characterized by the absence of the expression of the paternally inherited genes in chromosome 15 q11-13 region [1]. Te estimated prevalence of PWS is one in 10,000-25,000 live births [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations